Mining Context-Aware Significant Travel Sequences from Geotagged Social Media - Majid, Abdul; Chen, Ling; Mirza, Hamid; Hussain, Ibrar; Chen, Gencai (Proceedings of the AAAI Conference on Artificial Intelligence, 2021)
Geotagged photos of users on social media site, i.e., Flickr provide plentiful location-based data, which has been exploited for location-based services, such as mapping geotags to places and recommendation of personalized landmarks. As users’ preferences to visit a location or multiple locations in a certain sequence could be affected by their current temporal, and weather context. This paper considers the problem of mining context-aware significant semantic travel sequences from geotagged photos.